Sexual Harassment in Sports: Risk Factors Analysis from A Malaysian Perspective - Syahirah, Sharifah; S.S. , Syarifah Fathynah; Puspa Melati, Wan; Puteh, Fadilah; Abdul Hamid, Bahiyah; Ismail, Habibah (International Journal of Psychosocial Rehabilitation, 2020)
This article attempts to discuss the risk factors related to the occurrence of sexual harassment in sports. There have been many glaring cases of sexual harassment in sports reported in the Malaysian media. Unfortunately, most of these cases end up without any redress for the victim or punishment against the perpetrator. Hence, the objective of this article is to analyze the risk factors faced by sport practitioners and officers in handling as well as preventing sexual harassment and abuse in a few recent cases. A qualitative method was applied, and the primary data was collected through focus group sessions comprised of thirty-five (35) experts from sports institutions, enforcement officers, civil society representatives, athletes, and related government agencies. The result depicts fifteen (15) risk factors involved in handling cases related to sexual harassment and abuse in sports, particularly the lack of a code of practice and unclear procedures for those in charge. Since currently in Malaysia there are no specific rules related to handling sexual harassment in sports, previous cases were investigated under a penal code, and it has made it impossible for the victims to receive protection and redress.